Efektivitas Supervisi Akademik Kepala Sekolah Terhadap Peningkatan Kompetensi Pedagogik Guru - Yusrianti, Itel; Jamilus (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The role of the headteacher as an academic supervisor holds a strategic position in supporting the development of teachers’ pedagogical competencies, particularly in responding to curriculum changes and the demands for improved learning quality. This study aims to examine how the headteacher’s academic supervision is understood and positioned in the literature as an effort to strengthen teachers’ pedagogical competencies. This study employs a qualitative approach using a descriptive-analytical literature review method. Data sources were obtained from books, journal articles, and relevant previous research findings, which were analysed using content analysis techniques through the stages of reduction, presentation, and drawing conclusions. The findings indicate that academic supervision, when carried out in a planned, systematic, and continuous manner, has been reported in various previous studies to contribute positively to the development of teachers’ pedagogical competencies, particularly in the aspects of lesson planning, lesson delivery, classroom management, and learning assessment. Furthermore, supervision that is collaborative and constructive is seen as capable of fostering teachers’ professional reflection and improving teaching practices. These findings confirm that academic supervision by headteachers has the potential to be a key strategy in the development of teachers’ pedagogical competencies, although further empirical research is needed to measure its direct impact.